Analisis Ekonomi dan Geopolitik terhadap Jalur Pelayaran Internasional: Peran Strategis Terusan Suez terhadap Rantai Pasok Global - Safitri, Novita Andika (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The Suez Canal is one of the most strategic maritime infrastructures in the international trading system, connecting the Mediterranean Sea and the Red Sea while facilitating approximately 12–15 percent of global seaborne trade. This study aims to analyze the interaction between the economic and geopolitical dimensions of the Suez Canal and their implications for global supply chain resilience during the 2015–2024 period. Employing a qualitative descriptive-analytical approach based on a systematic literature review, data were collected from primary institutional sources, including official reports from the Suez Canal Authority (SCA), the United Nations Conference on Trade and Development (UNCTAD), and the International Maritime Organization (IMO), as well as secondary sources comprising scholarly articles indexed in Scopus and Web of Science. The analysis was conducted using content analysis and a geopolitical economy framework. The findings indicate that the Suez Canal functions not only as a logistics corridor but also as an arena of major geopolitical competition, particularly among the United States, China, and Russia. Disruptions to this route, as demonstrated by the MV Ever Given incident (2021), which caused trade losses estimated at USD 9.6 billion per day, and the Houthi attacks in the Red Sea (2023–2024), which triggered a threefold increase in shipping rates, exposed systemic vulnerabilities in global supply chains with significant consequences for inflation and food security across countries. This study concludes that excessive dependence on a single shipping route creates structural vulnerabilities, necessitating a transformation of supply chain management paradigms from lean models toward resilient models. Furthermore, it highlights the urgency of route diversification and the strengthening of national logistics capacities, particularly for developing countries such as Indonesia.